Application progress of magnetic resonance imaging in thyroid associated ophthalmopathy - Song, Yan; Li, Tuo; Tang, Wei; Lv, Qian; Zhang, Xing-xing; Zhou, Wei-yi; Shi, Yong-quan (Frontiers in Endocrinology, 2025)
Thyroid associated ophthalmopathy (TAO) is an autoimmune orbital disease associated with thyroid dysfunction, which may significantly impact the appearance and quality of life of patients. The course of TAO includes active stage and inactive stage, and the treatment methods are different in different stages. The clinical activity score is often used to evaluate the activity of TAO, but it is easy to be affected by subjective factors because it is based on the symptoms and signs of patients. Magnetic resonance imaging (MRI) can evaluate the postorbital tissue structure of TAO more objectively and accurately. A variety of MRI modalities have been used in the diagnosis and treatment of TAO. This article mainly summarizes the application of MRI in diagnosing TAO, assessing its activity, predicting treatment efficacy, and evaluating therapeutic outcomes, thereby providing clinicians with additional evidence-based options.